1996
DOI: 10.1016/0029-7844(96)00183-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of postoperative nasogastric tube decompression in gynecologic oncology patients undergoing intra-abdominal surgery

Abstract: Postoperative nasogastric tube decompression in gynecologic oncology patients undergoing extensive intra-abdominal surgery does not appear to provide any substantial benefit but significantly increases patient discomfort. As a result of this study, we have eliminated postoperative nasogastric decompression except in highly selected circumstances, such as extensive bowel surgery in patients with prior irradiation or substantial edema from bowel obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Moreover, nasogastric decompression has been routinely used to reduce the risk of postoperative complications such as acute gastric distension, ileus, wound dehiscence and anastomotic leak. However, in the last decade, some studies have argued against the necessity of nasogastric tube following surgeries for colorectal and gynecologic diseases [1,2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nasogastric decompression has been routinely used to reduce the risk of postoperative complications such as acute gastric distension, ileus, wound dehiscence and anastomotic leak. However, in the last decade, some studies have argued against the necessity of nasogastric tube following surgeries for colorectal and gynecologic diseases [1,2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…In colorectal surgery, after several series showed no benefit with NG tubes [10 -12], multiple prospective, randomized trials have confirmed there is no role for empirically placed NG tubes after elective colon operations [1,4,6,7]. Similar data were brought forth on major abdominal operations not involving the gastrointestinal tract such as gynecologic and aortic surgery [2,3]. Furthermore, patients who underwent more proximal bowel manipulation including small intestine anastomosis have been shown to not benefit from NG tubes [5,[13][14][15].…”
Section: Discussionmentioning
confidence: 68%
“…Empiric use of an NG tube is presumed to prevent abdominal distension, vomiting, and ileus, which may complicate the postoperative course. As abundance of prospective studies performed in the adult population have universally failed to support this practice [1][2][3][4][5][6][7]. This critical data clearly supports the omission of NG tubes after abdominal surgery in adults, but only scant reports exist in pediatric surgery [8,9].…”
Section: Introductionmentioning
confidence: 70%
“…The second example involves the routine use of nasogastric decompression after abdominal operations. The literature is replete with numerous randomized controlled trials (RCTs) that report no benefit in routine gastric decompression [62][63][64][65][66][67][68]. Furthermore, a Cochrane systemic review of the use of nasogastric tubes was published in 2007 and documented no benefit, and possible harm, with their routine use [69].…”
Section: Discussionmentioning
confidence: 99%